Biosurfactant from Streptomyces zaomyceticus HUS20 isolated from the Indian Himalayan Region (IHR) - A. Kishorekumar; M Radhakrishnan; Kaari Manigundan; S Sri Ranjani; Geetha Saravanan Thenmozhli; V. Gopikrishnan; Anita, P.; Kasem Soytong (International Journal of Agricultural Technology, 2025)
Actinobacteria, which are known to synthesize bioactive molecules with significant industrial and medicinal applications. In order to assess the possibility for producing biosurfactant (BS), this study sought to identify culturable actinobacteria from the high-altitude soils of Dugtu Village in the Indian Himalayan Region (IHR). Actinobacteria were isolated from pre-treated soil samples using nutrient agar, starch casein nitrate agar, and actinomycetes isolation agar, which were enhanced with 1% crude oil. Using the haemolytic assay, oil displacement test, emulsification activity, drop collapse assay, and penetration assay, morphologically different colonies were tested for the production of BS. Out of 58 actinobacterial cultures, strain HUS20 showed considerable emulsification index (65%) and a 30 mm zone in the oil displacement test. Using 16S rRNA sequencing, the strain HUS20 was shown to be 100% identical to Streptomyces zaomyceticus (GenBank accession: OQ996835.1). in HR LC MS analysis, the crude biosurfactant extract showed the presence of more than 164 metabolites. Additionally, the crude biosurfactant demonstrated strong antibacterial action against foodborne pathogens, with Bacillus cereus showing the greatest suppression (24 mm zone at 100 mg/ml). The potential of actinobacteria from harsh Himalayan habitats as a useful resource for the synthesis of biosurfactants is highlighted by this work. Streptomyces zaomyceticus HUS20 is a promising strain for isolation of potential biosurfactant molecule.
Keywords: Microbial bioremediation and biosurfactants; Enzyme Production and Characterization; Microbial Community Ecology and Physiology